Antiobesity and Hypoglycaemic Effects of Aqueous Extract of Ibervillea sonorae in Mice Fed a High-Fat Diet with Fructose. (17th November 2011) - Rivera-Ramírez, Fabiola; Escalona-Cardoso, Gerardo N.; Garduño-Siciliano, Leticia; Galaviz-Hernández, Carlos; Paniagua-Castro, Norma
Abstract : Obesity, type II diabetes, and hyperlipidaemia, which frequently coexist and are strongly associated with oxidative stress, increase the risk of cardiovascular disease. An increase in carbohydrate intake, especially of fructose, and a high-fat diet are both factors that contribute to the development of these metabolic disorders. In recent studies carried out in diabetic rats, authors reported that Ibervillea sonorae had hypoglycaemic activity; saponins and monoglycerides present in the plant could be responsible for the effects observed. In the present study, we determined the effects of an aqueous I. sonorae extract on a murine model of obesity and hyperglycaemia, induced by a high-calorie diet, and the relationship of these effects with hepatic oxidation. A high-fat diet over a period of 8 weeks induced weight gain in the mice and increased triglycerides and blood glucose levels. Simultaneous treatment with I. sonorae aqueous extracts, at doses of 100, 200, and 400 mg/kg, decreased triglycerides and glycaemia levels, prevented an increase in body weight in a dose-dependent manner, and decreased hepatic lipid oxidation at a dose of 200 mg/kg. These data suggest that the aqueous extract from I. sonorae root prevents obesity, dyslipidaemia, and hyperglycaemia induced by a hypercaloric diet; however, high doses may induce toxicity.